+0  
 
0
119
3
avatar

1. Let $r(\theta) = \frac{1}{1-\theta}$. What is $r(r(r(r(r(r(30))))))$ (where $r$ is applied $6$ times)?

 

2. If $f(a) = \frac{1}{1-a}$, find the product $f^{-1}(a) \times a \times f(a)$. (Assume $a \neq 0$ and $a \neq 1$.)

Guest Jul 17, 2018
 #1
avatar+90027 
+1

1.  \(r(\theta) = \frac{1}{1-\theta}$. What is $r(r(r(r(r(r(30))))))$ (where $r$ is applied $6$ times)? \)

 

r(30)  =  1 / (1 -30)  = 1/-29  = -1/29

r(r(30))  =  1  / (1 - (- 1/29))   = 1 / (29/29  + 1/29)  =  1 / (30/29)  =  29/30

r (r((r(30)))  = 1  / ( 1  - 29/30)  = 1 / ( 30/30 - 29/30)  =  1  / (1/30)  = 30

r (r(r(r(30))))  = 1 / (1 - ( 30) )  =   1/ (-29) = -1/29

r (r (r(r(r(30)))))  = 1 / ( 1  -  (-1/29) )  = ( 29/29 + 1/29)  =  1 / (30/29) = 29/30

r (r (r (r(r(r(30)))))) =  1 / (1 - (29/30) )  =  1 / ( 30/30 - 29/30)  =  1/(1/30)   =  30

 

 

cool cool cool

CPhill  Jul 17, 2018
 #2
avatar+90027 
+1

\(f(a) = \frac{1}{1-a}$, find the product $f^{-1}(a) \times a \times f(a)$. (Assume $a \neq 0$ and $a \neq 1$.)\)

 

 

 

Write     y  =  1  / ( 1 - a)        swap   a and y    and we want to get y by itself

 

a  = 1 / ( 1 - y)       multiply  both sides  by ( 1 - y)

 

a ( 1 - y)   =  1       divide both sides by  a

 

1 - y  =   1 /a       rearrange as

 

1 - 1 / a  = y          get a common denominator on the left side

 

(a - 1)  /  a  = y = f-1(a)       and this is the  inverse

 

So

 f-1 (a)  *  a  =     (a - 1) / a  * a     =  (a -1)

 

And this  product multiplied  by  f(a)  =   [ (a -1) ]  *  [ 1 / (1 - a) ]    =   [ (a -1) ]  * [ -  1 (a - 1) ]    =   -1

 

 

cool cool cool

f

CPhill  Jul 17, 2018
 #3
avatar+20025 
0

1. Let $r(\theta) = \frac{1}{1-\theta}$. What is $r(r(r(r(r(r(30))))))$ (where $r$ is applied $6$ times)?

 

\(\begin{array}{|rcll|} \hline r(\theta) &=& \dfrac{1}{1-\theta} \\ \hline r(r(\theta)) &=& \dfrac{1}{1-\dfrac{1}{1-\theta}} \\\\ &=& \dfrac{1-\theta}{1-\theta-1 } \\\\ &=& \dfrac{1-\theta}{ -\theta } \\\\ &=& \dfrac{\theta-1}{ \theta } = 1-\dfrac{1}{\theta} \\\\ \hline r(r(r(\theta))) &=& \dfrac{1}{1- (1-\dfrac{1}{\theta}) } \\\\ &=& \dfrac{1}{1- 1 + \dfrac{1}{\theta} }\\\\ &=& \dfrac{1}{ \dfrac{1}{\theta} } \\\\ &=& \theta \\ \hline r(r(r(r(\theta)))) &=& \dfrac{1}{1-\theta} \\ \hline \end{array}\)

 

This is a cycle:

\(\begin{array}{|r|r|c|} \hline \text{cycle} & & \ldots r(r(\theta) \\ \hline 1 & \text{once} & \color{red}\dfrac{1}{1-\theta} \\ \hline 1 & \text{twice} & \color{green}\dfrac{\theta-1}{ \theta } \\ \hline 1 & 3\text{ times} & \color{blue}\theta \\ \hline\hline 2 & 4\text{ times} & \color{red}\dfrac{1}{1-\theta} \\ \hline 2 & 5\text{ times} & \color{green}\dfrac{\theta-1}{ \theta } \\ \hline 2 & 6\text{ times} & \color{blue}\theta \\ \hline \ldots & \ldots& \ldots \\ \hline \end{array} \)

 

\(\text{So $r(r(r(r(r(r(\theta)))))) = \theta $ and $ r(r(r(r(r(r(30)))))) = \mathbf{30} $ } \)

 

2. If $f(a) = \frac{1}{1-a}$, find the product $f^{-1}(a) \times a \times f(a)$. (Assume $a \neq 0$ and $a \neq 1$.)

 

\(\begin{array}{|rcll|} \hline f{\color{red}(}f^{-1}(a){\color{red})} &=& a \\\\ f {\color{red}\Big(}\dfrac{a-1}{a}{\color{red}\Big)} &=& a \quad & | \quad \text{see table above } r\left(\dfrac{\theta-1}{\theta} \right) = \theta \\\\ \text{so } \\\\ f^{-1}(a) &=& \dfrac{a-1}{a} \\ \hline \end{array} \)

 

\(\begin{array}{|rcll|} \hline && f^{-1}(a) \times a \times f(a) \\\\ &=& \dfrac{a-1}{a}\times a \times \dfrac{1}{1-a} \\\\ &=& \dfrac{a-1}{1-a} \\\\ &=& -\dfrac{1-a}{1-a} \\\\ &=& -1 \\ \hline \end{array}\)

 

 

laugh

heureka  Jul 18, 2018
edited by heureka  Jul 18, 2018

25 Online Users

avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.